Alpha-synuclein release by neurons activates the inflammatory response in a microglial cell line. - Alvarez-Erviti, L; Couch, Y; Richardson, J; Cooper, J; Wood, M (2011)
The neurodegenerative process in Parkinson's disease (PD) is accompanied by the presence of a neuroinflammatory response, which has been suggested as one of the principal components involved in PD progression. In this report we assessed the inflammatory potential of alpha-synuclein, a protein central to PD pathogenesis, released by neurons on the mouse microglia cell line BV-2. BV-2 cells were treated with conditioned medium isolated from normal SH-SY5Y cells and clones that over-express WT or mutant A53T alpha-synuclein. Conditioned medium isolated from over-expressing clones induced the transcription and release of pro-inflammatory cytokines. Treatment of SH-SY5Y alpha-synuclein over-expressing cells with MPP+, the active metabolite of the neurotoxin MPTP, increased the inflammatory response in BV-2 cells. In contrast, the direct exposure of BV-2 cells to MPP+ failed to induce an inflammatory response. These results support the hypothesis that WT and A53T alpha-synuclein has an important role in the initiation and maintenance of inflammation in PD, through the activation of a pro-inflammatory response in microglial cells.